Status Of Mixed Atomes in Amorphy Hydrogened Silicon (Eurasian Journal of Learning and Academic Teaching, 2022)
The amorphous hydrogen bonded silicon atoms were introduced and their acceptor and donor sales properties formed in the silicon-locked zone were studied. In the atomi atomi in the atomi sifat, alsir er elements, and a new elements of the European elements, and the universal communication atomic, Erbus, Hydrogen, Golmy, Erbio, Hydrogan, Erbio, Hydrogan, Erbus, Hydrogeni, Erbi, Golitni, Erbus, Golitni, Erbekistan. Such a property of mixed European atoms has been found to be dependent on the formation of the 4f shell in it.